Radiocarbon date on megafauna from the late Pleistocene-early Holocene of Córdoba province, Argentina: stratigraphic and paleoclimatic significance - Cruz, Laura Edith (2010)
A radiocarbon date (7550 ± 60 $latex \small yr^{14} $C BP) was obtained from bone collagen of an extinct ground sloth (Scelidotherium leptocephalum) from the locality of Río Cuarto (Córdoba province, Argentina). The fossil remains were recovered from the La Invernada Formation (late Pleistocene- Holocene). The date presented in this paper is the first radiocarbon date obtained from megafauna in Córdoba province, Argentina. It supports the temporal assignation of the La Invernada Formation to the late Pleistocene-early Holocene, and it will allow correlation of these sediments with climatic events that took place during this time. Moreover, it is the youngest radiocarbon date from megamammals recorded in central Argentina.